SCCmec TYPING OF MRSA AND MRSE ISOLATES FROM NILAI - Visallinne, Ravichandar (2018)
The presence of mecA gene in methicillin-resistant Staphylococcus aureus and methicillin-resistant Staphylococcus epidermidis is the main reason for their resistance towards antibiotics derived from penicillin such as methicillin and cefoxitin. This gene encodes for penicillin-binding protein (PBP2a) which reduces the binding affinity of the bacteria towards β-lactam antibiotics. Previous studies show the isolation of numerous possible MRSA and MRSE isolates from healthy individuals in Nilai, as well as, from toilet door handles and handphones. However, only one isolate A/2016M/14 was identified to be mecA positive and of SCCmec type II. The other isolates were not investigated for mecA and SCCmec typing. Thus, this study was aimed to complete the molecular characterization of the remaining isolates through mecA amplification and SCCmec typing. Twenty-two out of thirty-two isolates were confirmed to be gram positive, clustered cocci with catalase production. These isolates were confirmed to be S. aureus and S. epidermidis by their growth on MSA. Eleven isolates of S. aureus and one S. epidermidis were found to be resistant to cefoxitin. Hence, these were confirmed as MRSA and MRSE isolates respectively. The DNA of these isolates was extracted using the cell lysis buffer and was subjected to mecA amplification using the MECA P4 and MECA P7 primers. Seven out of 12 isolates have the mecA gene and out of this, 6 were of SCCmec type II. This indicates the possible spread of a HA-MRSA clone within the community, as type II SCCmec is found in Hospital-acquired MRSA.